A Synthesis of Functionalized Dihydro-1H-pyrroles from Nef-Isocyanide Adducts and Enamines - Yavari, Issa; Hosseinpour, Reza; Pashazadeh, Ramin (Synlett, 2012)
α-Ketoimidoyl chlorides, obtained from α-addition of acyl chlorides onto alkyl isocyanides, are treated with enamines to afford 5-(alkylimino)-4-hydroxy-4,5-dihydro-1H-pyrrole-2,3,4-tricarboxylates and 2-(alkylimino)-3-hydroxy-2,3-dihydro-1H-pyrrole-3,4-dicarboxylates in good to excellent yields.
Keywords: Nef-isocyanide adduct; enaminone; imidoyl chloride; pyrrole; chemoselective reaction